Application of the Flexsim® discrete event simulator for virtualization of the VGR module (robot) of the physical simulator Fischertechnik® in a Digital Twin context - Nascimento, Adna Thais de Lima (2024)
This paper describes the process of virtualizing a 3-axis robot with a vacuum gripper (VGR - Vacuum Gripper Robot) for proof-of-concept pilot applications of the Digital Twin. The aim was to represent the dynamics of a board test environment including the characteristics of the physical twin, with the objective of investigating the use of the Flexsim® discrete event simulator for virtualization. The experimental research was carried out in a laboratory, in partnership with the State University of Amazonas (UEA) and its Technology and Innovation Center (HUB), in the Industry 4.0 Laboratory (I-4.0). The study used the Flexsim® simulator, a Delta AS228P PLC and the Fischertechnik® physical factory environment. The developed Digital Twin allowed the movement of parts between the modules of the physical simulator in a similar way to the real environment. The results prove the concept of Digital Twin and demonstrate the challenges of working with simulation models that reflect the characteristics of a real environment, as well as allow improvements to the developed system and generate opportunities for future work.